Restoring a Partial Maxillectomy Patient by an Implant-Supported Obturator on Two Implants: A Case Report - Eaheh Beyabanaki; Marzieh Alikhasi (Tehran University of Medical Sciences, 2018)
This article describes the prosthetic treatment of a patient suffering from a hemimaxillary defect after surgical resection of an adenoid cystic carcinoma (ACC) in the palate. The patient had also received therapeutic irradiation. One year after radiotherapy, three implants were placed in the remaining maxillary bone without any bone augmentation. One of the implants failed during the osseointegration period. The implant replacing the failed one also failed during prosthetic procedures. The patient was unwilling to undergo another surgical episode, and the final prosthesis was completed on the two remaining implants.